Austin and Tamara each completed the square of the quadratic equation 0=3x square - 15x + 6

Austin 0=3(x-5/2) square-51/4
Tamara 0=(x-5/2)square-17/4
Who is correct and show why

1 answer

mine:

3x^2 - 15x + 6 = 0
x^2 - 5x + .... = -2 + .....
x^2 - 5x + 25/4 = -2 + 25/4
(x-5/2)^2 = 17/4
(x - 5/2)^2 - 17/4 = 0

suppose I multiply by 3
3(x-5/2)^2 - 51/4 = 0

looks like they were both correct
Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions